2021
DOI: 10.3390/polym13111785
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Phthalic Anhydride with Epoxides Catalyzed by Amine-Bis(Phenolate) Chromium(III) Complexes

Abstract: The effect of ligand structure on the catalytic activity of amine-bis(phenolate) chromium(III) complexes in the ring-opening copolymerization of phthalic anhydride and a series epoxides was studied. Eight complexes differing in the donor-pendant group (R1) and substituents (R2) in phenolate units were examined as catalysts of the model reaction between phthalic anhydride and cyclohexane oxide in toluene. They were used individually or as a part of the binary catalytic systems with nucleophilic co-catalysts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…They observed that in the absence of a co-catalyst the Cr complex itself gave only 2% conversion of PA to polyester with a high degree of ether linkages. 26 However, upon addition of Lewis bases such as triphenylphosphine, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1-butylimidazole or DMAP, PA to polyester conversions up to 42% were obtained using equimolar amounts of catalyst to Lewis base and equimolar amount of PA to CHO in 0.5 mL of toluene at 110 °C and 1 h reaction time. 26 Reaction times of 4 h for the Cr complex with DMAP gave higher PA conversions of 95% with low ether linkages, molar masses up to 12.6 kg mol −1 and dispersities of 1.21.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They observed that in the absence of a co-catalyst the Cr complex itself gave only 2% conversion of PA to polyester with a high degree of ether linkages. 26 However, upon addition of Lewis bases such as triphenylphosphine, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1-butylimidazole or DMAP, PA to polyester conversions up to 42% were obtained using equimolar amounts of catalyst to Lewis base and equimolar amount of PA to CHO in 0.5 mL of toluene at 110 °C and 1 h reaction time. 26 Reaction times of 4 h for the Cr complex with DMAP gave higher PA conversions of 95% with low ether linkages, molar masses up to 12.6 kg mol −1 and dispersities of 1.21.…”
Section: Resultsmentioning
confidence: 99%
“…26 However, upon addition of Lewis bases such as triphenylphosphine, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1-butylimidazole or DMAP, PA to polyester conversions up to 42% were obtained using equimolar amounts of catalyst to Lewis base and equimolar amount of PA to CHO in 0.5 mL of toluene at 110 °C and 1 h reaction time. 26 Reaction times of 4 h for the Cr complex with DMAP gave higher PA conversions of 95% with low ether linkages, molar masses up to 12.6 kg mol −1 and dispersities of 1.21. Comparing these results to our catalyst system (Table 2, entry 2) the use of PPNCl obtains full conversion of PA to polyester within the same time frame with a M n of 8.1 kg mol −1 and Đ of 1.12.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Others have used Cr(III) catalysts for the ROCOP of https://doi.org/10.26434/chemrxiv-2023-sc5dl ORCID: https://orcid.org/0000-0001-8205-4130 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 epoxides such as CHO with PA. [25][26][27] Bester and co-workers used amino-bis(phenolate) Cr(III) complexes with 4-(dimethylamino)pyridine (DMAP) as a co-catalyst. 26 Boggioni used (salen)MCl catalysts, where M = Cr, Al, and Mn, and determined that formation of high molecular weight and Tg polymers required a pre-contact step between the catalyst and external nucleophilic co-catalyst was required.…”
Section: Introductionmentioning
confidence: 99%